THE IMPORTANCE OF PROBLEM EDUCATIONAL TECHNOLOGIES ORGANIZED IN UNIVERSITIES IN EDUCATION (American Journal of Interdisciplinary Research and Development, 2024)
One of the effective teaching technologies in the modern education system is problem-based learning. Problem-based learning corresponds to the goals of creative and active education of the individual. The essence of problem-based learning is the independent acquisition of new knowledge by creating a problem situation.